Sosialisasi Penyusunan Perencanaan Desa dan Anggaran Responsif Gender di Desa Duara, Kabupaten Lingga Kepulauan Riau - Wahyuni, Sri; Elsera, Marisa; Niko, Nikodemus (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
Law Number 6 of 2014 concerning Villages, it can be said that the government's commitment to improve village development by improving the quality of life of rural communities. This law has mandated the government to allocate village funds as a source of funds to manage the potential of villages. Although it has seen a positive impact on the Village Fund program so far, gender issues are often overlooked. In the implementation of the Village Fund program, it is also necessary to pay attention to the relationship between men and women, especially in the management of programs allocated from the Village Fund. Therefore, the Community Service (PKM) activities that we carry out are socialization of village planning preparation and gender responsive budgets in Duara village, Lingga district. The method of implementing community service activities is in the form of socialization activities with material on the preparation of a gender-responsive budget for village funds. If a village program held has considered gender equality in meeting the practical needs and strategic needs of both men and women, it can be said that the program has been successful and gender responsive.